Efficient and fast convergent consensus algorithms for faulty nodes tracking in distributed wireless sensor networks - Khan, Muhidulislam; Hossain, Rajkin (© 2016 IEEE, 2018)
This article was published in the IEEE Xplore [© 2016 IEEE] and the definite version is available at : http://doi.org/10.1109/CEEICT.2016.7873095 The Journal's website is at: http://ieeexplore.ieee.org/document/7873095/